AGRARIAN EXPANSION IN NORTHERN INDIA in EARLY MEDIEVAL PERIOD (c. A. D. 800-1200) - Sadaf, Syeda (IJRDO - Journal of Social Science and Humanities Research, 2016)
The present paper aims to study the phenomenon growth of agrarian expansion in Northern India during early medieval period (c. A. D.800-1200). Agriculture was the chief occupation of the primitive people. In fact cultivation of soil was one of the first forces in the development of civilization. The whole study is based on primary source of information. Primary source of information which is used is mainly in form of literary and epigraphic evidences. Secondary source of information is also used to corroborate the ideas gleaned from the primary sources. Since India remained mainly an agricultural country till the new economic policy of 1991 which started increasing the share of industrial output to the GDP leading to a remarkable shift from agricultural to industrial activities. From the study it is clear that the early medieval period (c. A. D. 800-1200) was by no means an exception to the historical nature of Indian economy which was primarily driven by agricultural activity. Northern India during early medieval period witnessed the multiplicity of monarchical polity, which further enhanced the process of agrarian expansion.